Acute Myocardial Infarction Patients Often Exhibit Abnormal Glucose Metabolism While Having No History of Diabetes - Cheragh Hussain, Muhammad Hussain Afridi, Akbar Shah, Shaista Kawanl, Nizamuddin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Upon check-in, tests were conducted to assess FBG, PPBG, and HbA1c levels in 100 patients. A majority of them, more than half, showed glucose processing issues, with FBG levels exceeding 100mg/dL. Additionally, 44 patients had increased HbA1c values. A follow-up after two weeks revealed that roughly 64% of patients still showed impaired glucose metabolism. Encouragingly, this number dropped to just 42% after a month. A concerning observation during the study was the heightened risk of glucose metabolism issues in patients with acute myocardial infarction, who had no prior history of diabetes. Hyperglycemia’s persistent chance must be considered for these individuals. Objectives: In Peshawar’s Hayatabad Medical Complex, the Department of Cardiology carried out a study on 100 patients with acute myocardial infarction who did not have diabetes history. The purpose was to investigate glucose metabolism by analyzing fasting blood glucose (FBG), postprandial blood glucose (PPBG), and HbA1c levels upon admission, after two weeks, and at one month. The findings of this study may provide insight into the impact of acute myocardial infarction on glucose metabolism. Methods: The Department of Cardiology at Hayatabad Medical Complex evaluated the records of 100 AMI patients who had no history of diabetes between January 2017 and January 2018 as part of a retrospective study. The patients’ mean age was 58.09 9.25 years, with ages ranging from 18 to 80. The patients’ files were consulted to get more detailed information about them, including their gender, age, medical history, and clinical features. Blood tests were done at various intervals such as at intake, two weeks, and one month following admission to assess FBG, PPBG, and HbA1c levels.. With the aid of percentages, chi-square tests, standard deviations, and averages, descriptive statistics were used to examine the data in SPSS 25. Results: Out of the 100 patients that participated in the study, males made up the majority with a whopping 72%, leaving the remaining 28% to be females. The average age of all participants was clocked at 58.09 (9.25) years. During admission, numerous test results indicated that 62% of patients showcased abnormal glucose metabolism with levels of FBG exceeding 100 mg/dL, while 44 of the patients demonstrated elevated levels of HbA1c. Following admission, the percentage of patients with abnormal glucose metabolism remained high, at 64%, two weeks afterward; however, this figure reduced to just 42% after a month. Conclusion: According to a recent study, non-diabetic patients with AMI are at risk of abnormal glucose metabolism, potentially leading to chronic hyperglycemia. This highlights the importance of monitoring glucose levels in such patients.Complications can arise from Acute Myocardial Infarction. It’s important to assess Risk Factors related to Glucose Metabolism, specifically Fasting Blood Glucose, Postprandial Blood Glucose, and HbA1c. Treatment is necessary to prevent further issues. Keywords: acute myocardial infarction, glucose metabolism, fasting blood glucose, postprandial blood glucose, HbA1c